STUDI IMPLEMENTASI PEMBELAJARAN KELAS RANGKAP DI DAERAH TERPENCIL - Linsurahman Takdir (DIADIK, 2020)
This study aims to: (1) describe the implementation of Multigrade Learning (PKR), (2) describe teacher obstacles in Multigrade Learning (PKR), (3) describe the efforts of teachers in Multigrade Learning (PKR) at SDN 127 Kaur District. The method used descriptive qualitative method. The subjects of this study were the principal and 3 teachers of SD N 127 Kaur. The technique of collecting data by means of interviews, observation and documentation. Data analysis in this study used an interactive method (analysis of Interactive Model), specifically data reduction, data presentation and conclusion. The conclusions of this study are: (1) Implementation of multigrade learning at SD N 127 Kaur has not been able to increase students' interest in learning. (2) Obstacles experienced by PKR teachers are lack of learning spaces and infrastructure. (3) the efforts of the teacher in overcoming obstacles, among others, by utilizing available learning resources and the surrounding environment